Implementation of Sharia Peer To Peer (P2P) Lending reviewed from the Principles of Tabadul Al Manafi and An Taradin - Riki Maulana; Neng Cahya Komala (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2026)
The rapid advancement of technology has significantly simplified access to various services, particularly within the financial industry. One notable development is the emergence and rapid growth of sharia-based peer-to-peer (P2P) lending fintech in Indonesia. This sub-sector represents an innovative approach adopted by financial institutions to facilitate financing and investment activities through digital platforms, thereby enhancing efficiency, accessibility, and financial inclusion. Nevertheless, in the context of Islamic economics, the pursuit of benefit (maslahah) remains the fundamental objective of all economic activities and must be consistently upheld. Accordingly, sharia-based P2P lending fintech is required to comply strictly with Islamic legal and ethical principles to ensure that its operations do not deviate from sharia norms. This study seeks to evaluate and examine the mechanisms of sharia-compliant P2P lending fintech by applying the principles of tabādul al-manāfi’ (mutual exchange of benefits) and an-tarāḍin (mutual consent among contracting parties). Using a normative legal research method, this study analyzes relevant statutory regulations, sharia guidelines, and legal doctrines. The analysis is conducted through a conceptual and evaluative approach, aiming to assess the extent to which existing fintech practices align with established sharia principles and contribute to equitable and ethical financial transactions.